The Antinomies of Administration: Politics-Administration and the Neglected Dichotomies of Administrative Thought - Reyes, Danilo dela Rosa (Philippine Journal of Public Administration; Vol 56 No 2 (2012), 2017)
The development of the study and practice of public administration has been remarkably characterized by antinomies and dichotomies. The article discusses the concept of antinomies and dichotomies as analytical tools that enrich the study and teaching of Public Administration. This essay is a review of how the discipline shaped its intellectual foundations as rooted on antinomic and dichotomous moorings. While the politics-administration dichotomy, which is now considered as the root theory in American Public Administration, has been traced to Wilson (1887), it was Waldo perhaps who gave prominent attention to propagating the antinomic tradition by identifying, outlining and discussing other contradictions and paradoxes that helped animate theorizing and discourse in the field. The article then proceeds to identify and discuss what can be considered as the neglected and overlooked antinomies and dichotomies in administrative thought today. Their significance in present day realities and problems, not just in administrative thought but in policymaking, dictates that they should be given more analytical scrutiny.
Keywords: public administration theory, antinomies, dichotomies, politics-administration dichotomy, administrative thought